Psychological need satisfaction across work and personal life: an empirical test of a comprehensive typology - Claude Fernet; Alexandre J. S. Morin; Marcus B. Mueller; Nicolas Gillet; Nicolas Gillet; Stéphanie Austin (Frontiers in Psychology, 2023)
IntroductionA comprehensive typology of the satisfaction of psychological needs at work and in personal life was developed and tested. The typology proposes five scenarios (Enriched, Middling, Impoverished, Work-Fulfilled, and Personal Life-Fulfilled) accounting for various profiles of employees showing distinct configurations of global and specific levels of need satisfaction at work and in personal life.MethodsThe scenarios were tested in a sample of 1,024 employees.ResultsUsing latent profile analysis, five profiles were identified that were consistent with four or the five scenarios, either aligned (Globally Satisfied, Globally Unsatisfied) or misaligned (Globally Satisfied at Work with High Relatedness, Globally Satisfied in Personal Life with High Autonomy, and Globally Satisfied in Personal Life with Low Autonomy) across domains. No profile corresponding to the Middling scenario was observed.DiscussionThe results indicate that perceived job and individual characteristics predicted membership in distinct profiles. More importantly, unlike the profile Globally Unsatisfied, the profile Globally Satisfied contributed substantially to higher well-being (vitality and lower psychological distress), and to more favorable job attitudes (job satisfaction and lower turnover intentions) and behaviors (self-rated job performance and lower absenteeism, presenteeism, and work injuries). Furthermore, two of the misaligned profiles were also substantially associated with highly desirable outcome levels.